1995
DOI: 10.1126/science.267.5194.51
|View full text |Cite
|
Sign up to set email alerts
|

High-Luminosity Blue and Blue-Green Gallium Nitride Light-Emitting Diodes

Abstract: Compact and efficient sources of blue light for full color display applications and lighting eluded and tantalized researchers for many years. Semiconductor light sources are attractive owing to their reliability and amenability to mass manufacture. However, large band gaps are required to achieve blue color. A class of compound semiconductors formed by metal nitrides, GaN and its allied compounds AIGaN and InGaN, exhibits properties well suited for not only blue and blue-green emitters, but also for ultraviol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
177
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(185 citation statements)
references
References 24 publications
1
177
1
1
Order By: Relevance
“…[1][2][3][4][5][6] Strain effects are particularly important for group-III nitrides because of the lack of native substrates. The growth on foreign substrates typically leads to the presence of built-in strain in heteroepitaxial nitride layers due to the difference in lattice parameters and thermal expansion coefficients between layers and substrates.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Strain effects are particularly important for group-III nitrides because of the lack of native substrates. The growth on foreign substrates typically leads to the presence of built-in strain in heteroepitaxial nitride layers due to the difference in lattice parameters and thermal expansion coefficients between layers and substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Blue LEDs (peak output at 450 nm) based on this rugged material are new items of commerce, and are inexpensive. They are optically quite efficient -more than 100 times brighter than Sic devices, the only other blue LED available [21]. We have shown that the GaN devices are capable of subnanosecond optical pulses.…”
Section: Optical Beaconsmentioning
confidence: 83%
“…The extension into the green and blue wavelengths completes the visible spectrum allowing semiconductor technology to be used for applications such as large full color displays and traffic lights. 2,3 Early research into the nitrides outlined several problem areas, which hindered efforts to produce devices based on III-V nitride technology. Particularly the lack of p-GaN made the fabrication of efficient optical devices based on p-n junctions impossible, though some LEDs based on metal-insulator-semiconductors were fabricated.…”
Section: Introductionmentioning
confidence: 99%